(untitled) (INNOVATIVE ECONOMY, 2025)
Fedoryshyna L.M., Dekaliuk O.V., Chaban S.R. MANAGEMENT OF CHANGES AT THE ENTERPRISE AS A REQUIREMENT OF THE TIME AND NECESSITY IN THE CONDITIONS OF AN UNSTABLE ENVIRONMENT Purpose. The aim of the article is to substantiate the theoretical foundations of the process of change management at the enterprise and outline its features and necessity in modern conditions. Methodology of research. The following research methods are used to achieve such purpose: analytical, monographic, abstract and logical, generalization – to study the essence of the concept of “management of changes” by various authors and to form one’s own vision of its essence, to describe the features of the change management process in wartime; tabular, graphical – to clearly present the essence of existing theories and approaches to explaining the causes of changes, as well as possible models of change management in modern conditions. Findings. The need for change management at the enterprise in modern conditions is actualized. The interpretation of the concept of “management of changes” by foreign and domestic authors is considered and its own definition is formed. It is established that change management in wartime is an extremely complex and responsible process that requires the use of specific models and strategies. This process includes adaptation to a rapidly changing environment, providing psychological support for employees, flexibility of organizational structures and effective use of technologies. Change management models that can be used by the management of Ukrainian enterprises in wartime are presented. In particular, such change management models as the J. Kotter model, ADKAR, resilience and crisis management models are useful tools for enterprises to successfully survive crisis situations and ensure their activities even in wartime. Originality. There was further development of the study of the essence of the concept of “management of changes at the enterprise”, which in the author’s interpretation should be considered as a systematic process of planning, implementing, monitoring and consolidating changes in the activities of the enterprise, aimed at adapting to external conditions and internal challenges, increasing the efficiency of activities, ensuring the competitiveness and sustainability of the enterprise in a rapidly changing environment. It is proved that change management at the enterprise in wartime is rather not a need, but a necessity and requirement of the time; the features of such management are outlined. Practical value. The results of the conducted research can be the basis for further research into the regarding of finding ways to improve the change management process at enterprises under martial law, taking into account industry specifics and areas of activity. Key words: changes, enterprise, change management, rapidly changing environment, war, causes of change, sources of change, change management models.